Socioeconomic Insights of Sago Smallholders in Sarawak : An Assessment on Demographic Status - Shamsul, Arsad; Rosita, Hamdan; Jerome, Kueh; Nur Zaimah, Ubaidillah; Josephine Yau, Tan Hwang; Audrey, Liwan; Mohammad Asraf, Abdullah; Rayenda Khresna, Brahmana (2022)
The sago palm (Metroxylon sagu Rottb.) is a perennial crop harvested for the starch yield accumulated in its trunk. Sarawak’s sago crops are dominated by sago smallholders, who play an important role in supplying raw materials to sago players, thereby accelerating sago industry activities that lead to state economic growth and income. This paper aims to identify the socioeconomic characteristics of sago smallholders in Sarawak. This study used a quantitative approach, employing a survey design with 697 respondents from Mukah division and Pusa district. Furthermore, observations on sago farming areas and Focus Group Discussions (FGD) with related stakeholders were conducted to understand and indicate the scenario of current sago smallholders’ livelihood and challenges. The descriptive statistical analysis was performed to analyse the results. The study demonstrates that the majority of farmers are older generations with minimal formal education, as evidenced by the farmers’ continued use of conventional techniques passed down through the generations in their sago farming activities. Thus, it is important to improve the sago smallholders’ socioeconomic livelihood lifestyle as to sustain in the sago industry.